A heat-accumulating and heat-preserving decorative integrated enclosure structure and a preparation method thereof
By using a multi-level pore size substrate and CaCO3 microcapsule encapsulation of phase change materials, the problem of poor balance between thermal insulation performance and strength in inorganic thermal insulation building envelopes has been solved, achieving efficient heat storage and transfer and improving the overall performance of building envelopes.
Patent Information
- Application Number
- CN202310862790.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-07-14
- Publication Date
- 2025-11-18
- Estimated Expiration
- 2043-07-14
AI Technical Summary
Existing inorganic thermal insulation enclosure structures suffer from poor balance between thermal insulation performance and strength, low heat transfer efficiency, and complex and costly encapsulation processes for phase change materials, making it difficult to achieve efficient heat storage and transfer.
A substrate with superimposed nano-, micron-, and millimeter-sized pores is used to encapsulate phase change materials with CaCO3 microcapsules. A thermally conductive film and decorative coating are attached to the surface. The substrate is prepared through an excitation-acid catalysis-alkali catalysis-surface modification-aging-drying process. Microcapsules are formed using urease-producing microbial liquid to achieve CaCO3 crystallization within the pores, thereby improving thermal conductivity and strength.
It achieves an organic combination of heat preservation, heat conduction and heat storage functions, improves the heat storage and transfer efficiency of the building envelope, enhances structural strength, and has a decorative effect.
Smart Images

Figure CN117047906B_ABST
Abstract
Description
Technical Field
[0001] This invention relates to an integrated thermal insulation and decorative enclosure structure and its preparation method, belonging to the fields of prefabricated buildings and green buildings. Background Technology
[0002] Improving the performance of building envelopes is a crucial approach to building energy conservation. Consequently, many functional building envelopes have emerged, such as fire-resistant and heat-insulating structures and phase-change heat storage structures. Currently, inorganic insulation boards, insulated walls, and insulated ceilings commonly used in green building often achieve their fire-resistant and heat-insulating effects through foaming or sacrificial filler methods to obtain porous structures. Compared to organic insulation envelopes, these inorganic insulation structures offer superior fire resistance and lower costs, but their overall insulation performance is weaker. Their simple internal pore structure makes it difficult to achieve both lightweight insulation and high strength. They can only passively reduce heat loss within the building and do not actively store or release excess heat from the building's internal and external structures. Therefore, phase-change heat storage structures have emerged as a new development in building envelope design, such as phase-change gypsum boards made from gypsum and phase-change paraffin, and phase-change concrete made by incorporating phase-change materials into concrete.
[0003] These heat-storage enclosure structures encapsulate phase change materials (PCMs) using inorganic or organic materials as carriers. For inorganic PCMs, common encapsulation methods include adsorption, melt blending, and microencapsulation. Adsorption is typically represented by heat-storage gypsum board, which is simple and inexpensive. However, the PCM is randomly distributed within the carrier, leading to multi-dimensional heat transfer that affects the rates of heat absorption and release, as well as the utilization of latent heat. Melt blending is simple and convenient but energy-intensive, and its inorganic carrier material has low thermal conductivity and is prone to phase separation, meaning the PCM easily leaks out. Microencapsulation is a mature technology with readily available raw materials, facilitating large-scale production. Encapsulating the PCM in spherical capsules effectively solves the problems of liquid-phase leakage and phase separation, expanding its application range. However, PCMs undergo volume changes of up to 15% before and after phase change, and repeated contraction and expansion reduce their lifespan. Therefore, high requirements are placed on the thickness and strength of the encapsulation layer, increasing the cost of microencapsulation. In addition, this type of material has very low thermal conductivity, and in many cases, thermal conductive agents need to be added, which increases costs and reduces heat storage capacity and temperature control capability.
[0004] This invention provides a novel integrated thermal insulation and decorative building envelope structure. Its innovation lies in the use of a substrate composed of three different pore sizes—nanoscale, microscale, and millimeter-scale—that contains both crystalline and glassy structures as the main body. Microcapsules with CaCO3 as the wall material and a solid-liquid phase change material as the core material are arranged within the pores of the main body material. A membrane material with high thermal conductivity is adsorbed onto the outer surface of the main body material. A decorative coating is sprayed onto the outer surface of the membrane material. The substrate of this invention possesses excellent thermal insulation properties, a certain degree of thermal conductivity, and high mechanical properties, organically combining thermal insulation, thermal conductivity, and high strength characteristics. The coating of this invention provides a decorative effect, while the thermally conductive membrane can directionally transfer heat from the building's interior and exterior to the substrate. The substrate provides insulation and a certain degree of thermal conductivity, allowing heat to propagate layer by layer along its pore structure. Simultaneously, the highly thermally conductive CaCO3 within the pores preferentially transfers heat to the phase change material, achieving the purpose of thermal storage. The product of this invention combines the functions of thermal insulation, directional heat conduction, centralized heat storage, high-strength enclosure, and decoration.
[0005] The purpose of this invention is to solve the above-mentioned problems and provide a novel integrated heat storage, insulation, and decorative enclosure structure and its preparation method. The innovations are: ① A substrate with specific pore structure and microscopic morphological characteristics is prepared through a process of "activation-acid catalysis-alkali catalysis-surface modification-aging-drying"; ② Microcapsules are prepared by first melting and mixing a phase change material with an emulsifier to form a microemulsion, and then mixing the microemulsion with a urease-producing microbial culture, a calcium source, and urea; ③ By adjusting the activation degree of the urease-producing microbial culture and the ratio of the calcium source and urea mixture, the microemulsion carries Ca... 2+ It penetrates into the pores of the substrate, displacing the liquid and gas in the pores of the substrate, and then the urease-producing microbial solution induces Ca... 2+ CaCO3 is generated by crystallization within the pores, achieving the goal of the microemulsion being perfectly embedded inside the pores and then spontaneously assembling into microcapsules. Summary of the Invention
[0006] According to a first aspect of the present invention, a heat storage, heat preservation and decorative integrated enclosure structure includes: a multi-level pore substrate, a microcapsule material, a thermally conductive film and an exterior coating;
[0007] The closed-cell space inside the multi-level porous substrate encapsulates microcapsule material; the thermally conductive film is attached to the surface of the multi-level porous substrate and fills the open pores on its surface; the outer coating is attached to the outer surface of the thermally conductive film.
[0008] The multi-level porous substrate is a solid composed of three different pore sizes: nano-scale, micro-scale, and millimeter-scale, and contains both crystalline and glassy structures. The silicon and aluminum powder is prepared by a process of "excitation-acid catalysis-alkali catalysis-surface modification-aging-drying".
[0009] The microcapsule material is prepared by first mixing a phase change material with an emulsifier to form a microemulsion, and then mixing the microemulsion with a urease-producing microbial culture, a calcium source, and a urea-containing mixed solution.
[0010] The wall material of the microcapsule material is CaCO3 with high thermal conductivity, and the core material is a heat storage material with phase change properties.
[0011] The microcapsule material encapsulated in the closed-pore space within the multi-level porous substrate is achieved by adjusting the activation level of the urease-producing microbial culture and the ratio of the mixed solution containing calcium source and urea, so that the microemulsion carries Ca... 2+ It penetrates into the pores of the multi-level porous substrate, displacing the liquid and gas in the internal pores of the multi-level porous substrate, and then the urease-producing microbial solution induces the Ca... 2+ CaCO3 is formed by crystallization within the pores;
[0012] The thermal conductivity of the thermal conductive film is >0.2 W / (m·K).
[0013] Preferably, the enclosure structure further includes: a connection device for connecting the enclosure structure to other building components and a connection device for connecting the enclosure structures to each other.
[0014] According to a second aspect of the present invention, a method for preparing an integrated thermal insulation and decorative enclosure structure includes the following steps: S1. After uniformly mixing industrial solid waste residue and natural crystal stone powder, they are ground together to 150 mesh to 200 mesh to obtain a mixed powder; the mass ratio of the industrial solid waste residue to the natural crystal stone powder is 1:(0.3-2.5);
[0015] S2. Mix the mixed powder from S1, the spent phosphoric acid polishing liquid or (water glass / NaOH) solution, and water, and stir evenly within 20 minutes to obtain mixture A; the modulus of the water glass is 1.5-3.5; the mass of the NaOH is less than 0.5 times the mass of the water glass; the mass of the water is 4-10 times the mass of the mixed powder.
[0016] S3. Mix the mixture A, silicon source, and water glass, and gradually add hydrochloric acid until the pH of the mixture drops to 1-4. Then continue stirring for 10-15 minutes to obtain sol A.
[0017] S4. Melt the phase change material to a liquid state, then mix it with an emulsifier solution, keeping the temperature above the melting point of the phase change material and stirring rapidly for 10-120 minutes to ensure uniform mixing of the liquid phase change material and the emulsifier; then slowly add a mixed solution containing calcium source and urea while stirring simultaneously; still keeping the temperature above the melting point of the phase change material and continuing to stir for 20-240 minutes to obtain a stable microemulsion;
[0018] S5. Add urease-producing microbial culture to the microemulsion and stir continuously to obtain mixture B;
[0019] S6. Add mixture B to sol A, stir continuously, and adjust the pH value to 8-11 to obtain mixed sol B;
[0020] S7. Pour the mixed sol B from S6 into the mold of the enclosure structure, and then age it at 15-60℃ for more than 2 hours to obtain gel material A;
[0021] S8. Add anhydrous ethanol to gel material A obtained in S7, and then age it at 15-60℃ for more than 24 hours to obtain gel material B.
[0022] S9. Soak gel material B in running water at a temperature of 10-45℃ for 10-20 hours to obtain a gel solid.
[0023] S10. The gel solid described in S9 is dried in an environment of 60°C to obtain the main body of the enclosure structure;
[0024] S11. Coat the surface of the main body of the enclosure structure described in S10 with a dense film with high thermal conductivity;
[0025] S12. Mix real stone paint and water and spray it onto the surface of the enclosure structure. Then dry it in the range of room temperature to 80°C to obtain an integrated heat storage, heat preservation and decoration enclosure structure.
[0026] Preferably, the industrial solid waste residue in S1 includes one or more of the following: fly ash, red mud, silica fume, steel slag, fly ash, and washed fly ash; and the natural crystalline stone powder in S1 includes one or more of the following: tuff, tuff lava, andesite, natural zeolite, and kaolin.
[0027] Preferably, in step S3, mixing the mixture A, silicon source, and water glass, and gradually adding hydrochloric acid to it includes: first mixing the mixture A, silicon source, and water glass in a volume ratio of 1:(0-0.2):(1-6), then gradually adding 5-25 mol / L hydrochloric acid solution, and simultaneously monitoring the change in pH value until the pH value drops to the range of 1-4.
[0028] Preferably, the silicon source includes one or two of the following: TEOS (tetraethyl silicate), a product obtained by high-temperature calcination of a mixture of silicon-aluminum material and NaCO3.
[0029] Preferably, the product obtained by high-temperature calcination of silicon-aluminum material mixed with NaCO3 includes: pulverizing fly ash or kaolin to 120-200 mesh to obtain silicon-aluminum mixed powder; mixing silicon-aluminum mixed fly ash and NaCO3 at a mass ratio of 1:(0.5-2) and calcining at 600-900℃ for 60-300 min.
[0030] Preferably, in step S4, melting the phase change material into a liquid state includes heating a solid-liquid phase change material with a phase change temperature between 12-30°C into a liquid state.
[0031] Preferably, the solid-liquid phase change material with a phase change temperature between 12-30℃ includes one or more of paraffin wax, fatty acids, inorganic salt hydrates, and polyols.
[0032] Preferably, the emulsifier solution in S4 comprises: a liquid obtained by mixing SMA (polystyrene-maleic anhydride copolymer), NaOH and water in a mass ratio of 5:(0.5-1.5):(50-80) and stirring at 90°C for 15 min.
[0033] Preferably, the emulsifier solution in S4 comprises: a liquid obtained by mixing one of SDS (sodium dodecyl sulfate) or SDBS (sodium dodecylbenzene sulfonate) with water at a mass ratio of 1:(50-80) and stirring at 90°C for 15 min.
[0034] Preferably, the mixed solution containing calcium source and urea is slowly added in S4, comprising: a mixed solution prepared by urea, calcium salt, nutrient broth, ammonium chloride, sodium bicarbonate and water in a mass ratio of 3:(2-6):(0-1):(0-4):(2-3):500.
[0035] Preferably, after S1 and before S4, the process further includes: mixing foaming agent, foam stabilizer, and water in a mass ratio of 1:0.6:20 and injecting the mixture into a foaming machine, starting the foaming machine, and producing gas foam; mixing the gas foam with the mixture A in S2 or the sol A in S3, and stirring until homogeneous.
[0036] Preferably, before starting the foaming machine, the process further includes: introducing waste CO2 gas emitted during industrial production into the foaming machine.
[0037] Preferably, adjusting the pH value to 8-11 in step S6 includes adding ammonia or urease microbial solution to the mixture of mixture B and sol A.
[0038] Preferably, in step S7, pouring the mixed sol B into the mold of the enclosure structure includes: pouring the mixed sol B into the wall mold, the floor mold, and the ceiling mold.
[0039] Preferably, before step S7, the method further includes: arranging ribs with lightweight and thermally conductive characteristics in the inner cavity of the mold.
[0040] Preferably, the dense, high thermal conductivity film in S11 includes films prepared from one or more of graphite materials, carbon fiber materials, calcium carbonate materials, or metallic materials.
[0041] Preferably, in step S11, the main body surface is coated with a dense, high thermal conductivity film, which includes placing the main body in a low-pressure immersion device. A pressure of 0-0.2 MPa is applied through this low-pressure immersion device to force the microbial solution and binder into the pores on the surface of the insulation board main body. Attached Figure Description
[0042] Figure 1 This is a schematic diagram of the process of the present invention. Detailed Implementation
[0043] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0044] A thermal insulation and decorative integrated enclosure structure includes: a multi-level pore substrate, a microcapsule material, a thermally conductive film, and an exterior coating.
[0045] Microcapsule materials are encapsulated in the closed-pore spaces inside the multi-level porous substrate; a thermally conductive film is attached to the surface of the multi-level porous substrate and fills the open pores on its surface; an external coating is attached to the outer surface of the thermally conductive film.
[0046] The multi-level pore size substrate is prepared from silicon and aluminum powder through a process of "excitation-acid catalysis-base catalysis-surface modification-aging-drying";
[0047] Multi-level porous substrates are solids composed of three different pore sizes: nanoscale, microscale, and millimeter scale, and contain both crystalline and glassy structures.
[0048] Microcapsule materials are prepared by first mixing phase change materials with emulsifiers to form microemulsions, and then mixing the microemulsions with urease-producing microbial inoculum, a calcium source and a urea mixed solution.
[0049] The wall material of the microcapsule material is CaCO3 with high thermal conductivity, and the core material is a heat storage material with phase change properties.
[0050] The microcapsule material encapsulated within the closed-pore space of the multi-level porous substrate is achieved by adjusting the activation level of the urease-producing microbial culture and the ratio of the mixed solution containing calcium source and urea, so that the microemulsion carries Ca... 2+ It penetrates into the pores of a multi-level porous substrate, displacing the liquid and gas inside the pores, and then the urease-producing microbial solution induces Ca... 2+ CaCO3 is formed by crystallization within the pores;
[0051] The thermal conductivity of the thermally conductive film is >0.2 W / (m·K).
[0052] As a technical optimization of the present invention, a method for preparing a heat storage, heat preservation and decorative integrated enclosure structure includes the following steps: S1. After mixing industrial solid waste residue and natural crystal stone powder evenly, grind them together to 150 mesh to 200 mesh to obtain mixed powder; the mass ratio of industrial solid waste residue to natural crystal stone powder is 1:(0.3-2.5);
[0053] S2. Mix the mixed powder from S1, the spent phosphoric acid polishing solution or (water glass / NaOH) solution, and water, and stir evenly within 20 minutes to obtain mixture A; the modulus of water glass is 1.5-3.5; the mass of NaOH is less than 0.5 times the mass of water glass; the mass of water is 4-10 times the mass of the mixed powder.
[0054] S3. Mix the mixture A, silicon source, and water glass, and gradually add hydrochloric acid until the pH of the mixture drops to 1-4. Then continue stirring for 10-15 minutes to obtain sol A.
[0055] S4. Melt the phase change material to a liquid state, then mix it with an emulsifier solution, keeping the temperature above the melting point of the phase change material and stirring rapidly for 10-120 minutes to ensure uniform mixing of the liquid phase change material and the emulsifier; then slowly add a mixed solution containing calcium source and urea while stirring simultaneously; still keeping the temperature above the melting point of the phase change material and continuing to stir for 20-240 minutes to obtain a stable microemulsion;
[0056] S5. Add urease-producing microbial culture to the microemulsion and stir continuously to obtain mixture B;
[0057] S6. Add mixture B to sol A, stir continuously, and adjust the pH value to 8-11 to obtain mixed sol B;
[0058] S7. Pour the mixed sol B from S6 into the mold of the enclosure structure, and then age it at 15-60℃ for more than 2 hours to obtain gel material A;
[0059] S8. Add anhydrous ethanol to gel material A obtained in S7, and then age it at 15-60℃ for more than 24 hours to obtain gel material B.
[0060] S9. Soak gel material B in running water at a temperature of 10-45℃ for 10-20 hours to obtain a gel solid.
[0061] S10. Dry the S9 gel solid at 60°C to obtain the main body of the enclosure structure;
[0062] S11. Coat the surface of the main body of the S10 enclosure structure with a dense, high thermal conductivity film;
[0063] S12. Mix real stone paint and water and spray it onto the surface of the enclosure structure. Then dry it in the range of room temperature to 80°C to obtain an integrated heat storage, heat preservation and decoration enclosure structure.
[0064] As a technical optimization scheme of the present invention, the industrial solid waste slag material in S1 includes one or more of the following: fly ash, red mud, silica fume, steel slag, fly ash, and washed fly ash. The natural crystalline stone powder in S1 includes one or more of the following: tuff, tuff lava, andesite, natural zeolite, and kaolin. In S3, the mixture of liquid A, silicon source, and water glass is mixed, and hydrochloric acid is gradually added to it. The mixture of liquid A, silicon source, and water glass is first mixed in a volume ratio of 1:(0-0.2):(1-6), and then 5-25 mol / L hydrochloric acid solution is gradually added dropwise, while the pH value is monitored simultaneously until the pH value drops to the range of 1-4. The silicon source includes one or two of the following: TEOS (tetraethyl silicate), and the product of high-temperature calcination of silicon aluminum material mixed with NaCO3.
[0065] As a technical optimization of the present invention, the product of high-temperature calcination of silicon-aluminum material mixed with NaCO3 includes: pulverizing fly ash or kaolin to 120-200 mesh to obtain silicon-aluminum mixed powder; mixing silicon-aluminum mixed fly ash and NaCO3 at a mass ratio of 1:(0.5-2), and calcining in an environment of 600-900℃ for 60-300 min; heating a solid-liquid phase change material with a phase change temperature between 12-30℃ to a liquid state; the solid-liquid phase change material with a phase change temperature between 12-30℃ includes: paraffin wax, fatty acids, inorganic hydrates, and polyols. One or more types of emulsifier solutions in S4 include: a liquid obtained by mixing SMA (polystyrene-maleic anhydride copolymer), NaOH, and water in a mass ratio of 5:(0.5-1.5):(50-80) and stirring at 90°C for 15 min; an emulsifier solution in S4 includes: a liquid obtained by mixing one of SDS (sodium dodecyl sulfate) or SDBS (sodium dodecylbenzene sulfonate) with water in a mass ratio of 1:(50-80) and stirring at 90°C for 15 min; and a mixed solution containing a calcium source and urea slowly added to S4, including: a mixture of... A mixed solution prepared by mixing urea, calcium salt, nutrient broth, ammonium chloride, sodium bicarbonate, and water in a mass ratio of 3:(2-6):(0-1):(0-4):(2-3):500, after S1 and before S4, further includes: mixing foaming agent, foam stabilizer, and water in a mass ratio of 1:0.6:20 and injecting the mixture into a foaming machine, starting the foaming machine to produce gas foam; mixing the gas foam with mixture A in S2 or sol A in S3 and stirring evenly, before starting the foaming machine, further includes: introducing waste CO2 gas emitted during industrial production into the foaming machine, in S6... Adjusting the pH value to 8-11 includes: adding ammonia or urease microbial solution to the mixture of mixture B and sol A; pouring the mixed sol B into the mold of the enclosure structure in step S7 includes: pouring the mixed sol B into the wall mold, floor mold, and ceiling mold; arranging lightweight, thermally conductive reinforcing materials in the inner cavity of the mold; the dense, high thermal conductivity film in step S11 includes: a film prepared from one or more of graphite materials, carbon fiber materials, calcium carbonate materials, or metal materials; coating the main body surface with a dense, high thermal conductivity film in step S11 includes: placing the main body in a low-pressure immersion device. Applying a pressure of 0-0.2 MPa through the low-pressure immersion device, the microbial solution and binder are forced into the pores on the surface of the insulation board main body; the enclosure structure further includes: a connection device between the enclosure structure and other building components, and a connection device between the enclosure structures themselves.
[0066] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above, and that the invention can be implemented in other specific forms without departing from its spirit or essential characteristics. Therefore, the embodiments should be considered in all respects as exemplary and non-limiting, and the scope of the invention is defined by the appended claims rather than the foregoing description. Thus, all variations falling within the meaning and scope of equivalents of the claims are intended to be included within the present invention. No reference numerals in the claims should be construed as limiting the scope of the claims.
[0067] Furthermore, it should be understood that although this specification describes embodiments, not every embodiment contains only one independent technical solution. This narrative style is merely for clarity. Those skilled in the art should consider the specification as a whole, and the technical solutions in each embodiment can also be appropriately combined to form other embodiments that can be understood by those skilled in the art.
Claims
1. A method for preparing an integrated thermal insulation and decorative enclosure structure, characterized in that: Includes the following steps: S1. After uniformly mixing industrial solid waste residue and natural crystal stone powder, grind them to 150 to 200 mesh to obtain mixed powder; the mass ratio of the industrial solid waste residue to the natural crystal stone powder is 1:(0.3-2.5); S2. Mix the mixed powder from S1, the spent phosphoric acid polishing solution or water glass / NaOH solution, and water, and stir evenly within 20 minutes to obtain mixture A; the modulus of the water glass is 1.5-3.5; the mass of the NaOH is less than 0.5 times the mass of the water glass; the mass of the water is 4-10 times the mass of the mixed powder. S3. Mix the mixture A, silicon source, and water glass, and gradually add hydrochloric acid until the pH of the mixture drops to 1-4. Then continue stirring for 10-15 minutes to obtain sol A. S4. Melt the phase change material to a liquid state, then mix it with an emulsifier solution, keeping the temperature above the melting point of the phase change material and stirring rapidly for 10-120 minutes to ensure uniform mixing of the liquid phase change material and the emulsifier; then slowly add a mixed solution containing calcium source and urea while stirring simultaneously; still keeping the temperature above the melting point of the phase change material and continuing to stir for 20-240 minutes to obtain a stable microemulsion; S5. Add urease-producing microbial culture to the microemulsion and stir continuously to obtain mixture B; S6. Add mixture B to sol A, stir continuously, and adjust the pH value to 8-11 to obtain mixed sol B; S7. Pour the mixed sol B from S6 into the mold of the enclosure structure, and then age it at 15-60℃ for more than 2 hours to obtain gel material A; S8. Add anhydrous ethanol to gel material A obtained in S7, and then age it at 15-60℃ for more than 24 hours to obtain gel material B. S9. Soak gel material B in running water at a temperature of 10-45℃ for 10-20 hours to obtain a gel solid. S10. The gel solid described in S9 is dried in an environment of 60°C to obtain the main body of the enclosure structure; S11. Coat the surface of the main body of the enclosure structure described in S10 with a dense film with high thermal conductivity; S12. Mix real stone paint and water and spray it onto the surface of the enclosure structure. Then dry it in the range of room temperature to 80°C to obtain an integrated heat storage, heat preservation and decoration enclosure structure.
2. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, The industrial solid waste residue in S1 includes one or more of the following: fly ash, red mud, silica fume, steel slag, fly ash, and washed fly ash. The natural crystalline stone powder in S1 includes one or more of the following: tuff, tuff lava, andesite, natural zeolite, and kaolin.
3. The method for preparing a heat storage, insulation, and decorative integrated enclosure structure according to claim 1, characterized in that, In step S3, mixing the mixture A, silicon source, and water glass, and gradually adding hydrochloric acid to it includes: first mixing the mixture A, silicon source, and water glass in a volume ratio of 1:(0-0.2):(1-6), then gradually adding 5-25 mol / L hydrochloric acid solution, while simultaneously monitoring the pH value until the pH value drops to the range of 1-4.
4. The method for preparing a heat storage, insulation, and decorative integrated enclosure structure according to claim 1, characterized in that, The silicon source includes one or two of the following: tetraethyl silicate, a product obtained by high-temperature calcination of a mixture of silicon-aluminum materials and NaCO3.
5. The method for preparing a heat storage, insulation, and decorative integrated enclosure structure according to claim 4, characterized in that, The product of high-temperature calcination of silicon-aluminum materials mixed with NaCO3 includes: crushing fly ash or kaolin to 120-200 mesh to obtain silicon-aluminum mixed powder; mixing silicon-aluminum mixed fly ash with NaCO3 at a mass ratio of 1:(0.5-2) and calcining at 600-900℃ for 60-300 min.
6. The method for preparing a heat storage, insulation, and decorative integrated enclosure structure according to claim 1 is characterized in that, The step S4, melting the phase change material into a liquid state, includes heating a solid-liquid phase change material with a phase change temperature between 12-30°C into a liquid state.
7. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 6 is characterized in that, The phase transition temperature of the solid is between 12-30℃. Liquid phase change materials include one or more of the following: paraffin wax, fatty acids, inorganic salt hydrates, and polyols.
8. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1 is characterized in that, The emulsifier solution described in S4 comprises: a liquid obtained by mixing polystyrene maleic anhydride copolymer, NaOH and water in a mass ratio of 5:(0.5-1.5):(50-80) and stirring at 90°C for 15 min.
9. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1 is characterized in that, The emulsifier solution described in S4 includes: a liquid obtained by mixing sodium dodecyl sulfate or sodium dodecylbenzene sulfonate with water at a mass ratio of 1:(50-80) and stirring at 90°C for 15 minutes.
10. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1 is characterized in that, The S4 step involves the slow addition of a mixed solution containing a calcium source and urea, comprising: A mixed solution prepared by mixing urea, calcium salt, nutrient broth, ammonium chloride, sodium bicarbonate and water in a mass ratio of 3:(2-6):(0-1):(0-4):(2-3):
500.
11. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, The process after S1 and before S4 further includes: mixing foaming agent, foam stabilizer, and water in a mass ratio of 1:0.6:20 and injecting the mixture into a foaming machine, starting the foaming machine, and producing gas foam; mixing the gas foam with the mixture A in S2 or the sol A in S3 and stirring until homogeneous.
12. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 11, characterized in that, Before starting the foaming machine, the process further includes: introducing waste CO2 gas emitted during industrial production into the foaming machine.
13. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, Adjusting the pH value to 8-11 in step S6 includes adding ammonia or urease microbial solution to the mixture of mixture B and sol A.
14. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, The step S7, which involves pouring the mixed sol B into the mold of the enclosure structure, includes: pouring the mixed sol B into the wall mold, the floor mold, and the ceiling mold.
15. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, Before step S7, the method further includes: arranging ribs with lightweight and thermally conductive characteristics in the inner cavity of the mold.
16. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, The dense, high thermal conductivity film in S11 includes a film prepared from one or more of graphite materials, carbon fiber materials, calcium carbonate materials, or metallic materials.
17. The method for preparing a heat-storing, heat-insulating, and decorative integrated enclosure structure according to claim 1, characterized in that, The process of coating the main body surface with a dense, high thermal conductivity film in S11 includes: placing the main body in a low-pressure immersion device, applying a pressure of 0-0.2 MPa through the low-pressure immersion device, and injecting the microbial liquid and binder into the pores on the surface of the insulation board main body.
18. The integrated heat-storage, heat-insulating, and decorative enclosure structure prepared by the method according to any one of claims 1-17, characterized in that, include: Multi-level pore size substrates, microcapsule materials, thermally conductive films, and exterior coatings; The closed-pore space inside the multi-level porous substrate encapsulates microcapsule materials; The thermally conductive film is attached to the surface of a multi-level pore substrate and fills the open pores on its surface. The exterior coating is attached to the outer surface of the thermally conductive film; The multi-level porous substrate is a solid composed of three different pore sizes: nano-scale, micro-scale, and millimeter-scale, and contains both crystalline and glassy structures. It is prepared through a process of "excitation-acid catalysis-base catalysis-surface modification-aging-drying". The microcapsule material is prepared by first mixing a phase change material with an emulsifier to form a microemulsion, and then mixing the microemulsion with a urease-producing microbial culture, a calcium source, and a urea-containing mixed solution. The wall material of the microcapsule material is CaCO3 with high thermal conductivity, and the core material is a heat storage material with phase change characteristics. The closed-pore space inside the multi-level porous substrate encapsulates microcapsule material. By adjusting the activation degree of the urease-producing microbial culture and the ratio of the mixed solution containing calcium source and urea, the microemulsion carries Ca... 2+ It penetrates into the pores of the multi-level porous substrate, displacing the liquid and gas in the internal pores of the multi-level porous substrate, and then the urease-producing microbial solution induces the Ca... 2+ CaCO3 is formed by crystallization within the pores; The thermal conductivity of the thermal conductive film is >0.2 W / (m·K).
19. The integrated heat storage, insulation, and decorative enclosure structure according to claim 18, characterized in that, The enclosure structure further includes: a connection device for connecting the enclosure structure to other building components and a connection device for connecting the enclosure structures to each other.
Citation Information
Patent Citations
Phase-change thermal-storage intelligent temperature-control wall material and preparation method thereof
CN102992703A
Graphene / phase-change microcapsule composite material and preparation method and application thereof
CN109735306A